Positive electrode active material layer, electrode, and solid-state battery
By using characteristic vinylidene fluoride homopolymer or copolymer as the binder in the positive electrode active material layer of semi-solid or all-solid battery, the problem of high interface resistance between the current collector and the electrode active material layer is solved, and more efficient charging and discharge is achieved and corrosion risks are reduced.
Patent Information
- Application Number
- CN202380054499.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-07-20
- Publication Date
- 2025-03-11
AI Technical Summary
In semi-solid or all-solid state batteries, the interface resistance between the current collector and the electrode active material layer is high, resulting in poor charging and discharging efficiency and a risk of corrosion.
Interfacial resistance is suppressed by adding characteristic vinylidene fluoride homopolymer or copolymer to the positive electrode active material layer as the binder. The adhesive has an intrinsic viscosity of 3.5 dL/g or less, and specifically includes polymer (C-a) and polymer (C-b).
It effectively suppresses the interface resistance between the current collector and the electrode active material layer, improves the charge and discharge efficiency, and reduces the risk of metal corrosion.
Smart Images

Figure BDA0005246749240000141 
Figure BDA0005246749240000151 
Figure BDA0005246749240000161
Abstract
Description
Technical Field
[0001] The invention relates to a positive electrode active material layer, an electrode and a solid-state battery. Background Art
[0002] In the previous secondary batteries containing electrolytes, when the battery cell is abnormal such as an internal short circuit of the battery cell or the temperature of the battery cell rises, the possibility of fire is extremely high. Therefore, from the perspective of improving the safety of the battery cell, research has been conducted on semi-solid batteries or all-solid batteries that convert most or all of the electrolyte into a solid electrolyte. Semi-solid batteries or all-solid batteries are considered to simplify safety devices and have excellent manufacturing costs and productivity because the electrolyte containing a flammable organic solvent is very small or zero.
[0003] The active material layer of the electrode of a semi-solid battery or a fully solid battery is assumed to further contain a solid electrolyte in addition to the active material, conductive additive, and binder constituting the electrode active material layer of a conventional secondary battery. However, compared with the case where an electrolyte is used as an electrolyte, the movement of lithium ions and electrons becomes difficult, so there is a problem of increasing the interface resistance between the current collector and the electrode active material layer.
[0004] On the other hand, for example, Patent Document 1 discloses a positive electrode material for a lithium-sulfur solid battery containing sulfur, a conductive material, a binder, and an ionic liquid or a solvated ion for the purpose of suppressing the interface resistance between a solid electrolyte and an electrode.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2017-168435 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] However, when an ionic liquid is used, the metal contained in the electrode current collector corrodes, and sometimes good charge and discharge efficiency cannot be achieved. Therefore, a technology is needed to suppress the interface resistance between the current collector and the electrode active material layer even without using an ionic liquid.
[0010] The present invention is completed in view of the above-mentioned problems, and its purpose is to provide a positive electrode active material layer that can form a positive electrode with suppressed interface resistance between the collector and the electrode active material, an electrode having the positive electrode active material layer, and a semi-solid battery or all-solid battery having the electrode.
[0011] Solutions for solving problems
[0012] In order to solve the above problems, the present inventors conducted repeated and intensive research and found that the above problems can be solved by including a homopolymer or copolymer of vinylidene fluoride having a specific characteristic viscosity as a binder in a positive electrode active material layer containing a positive electrode active material and a solid electrolyte, thereby completing the present invention.
[0013] The embodiment of the present invention relates to the following positive electrode active material layer, electrode, and semi-solid-state battery or all-solid-state battery, which contain a positive electrode active material (A), a solid electrolyte (B), and a binder (C).
[0014] [1] A positive electrode active material layer comprising a positive electrode active material (A), a solid electrolyte (B) and a binder (C), wherein the binder (C) is a polymer (Ca) or a polymer (Cb) described below.
[0015] Polymer (Ca): a homopolymer of vinylidene fluoride having an intrinsic viscosity of 3.5 dL / g or less.
[0016] Polymer (Cb): a vinylidene fluoride copolymer containing structural units derived from vinylidene fluoride and structural units derived from hexafluoropropylene, having an intrinsic viscosity of 1.3 dL / g to 4.0 dL / g, wherein the structural units derived from hexafluoropropylene account for 8.0% by mass or less, based on 100.0% by mass of all structural units of the vinylidene fluoride copolymer.
[0017] [2] The positive electrode active material layer according to [1], wherein the intrinsic viscosity of the polymer (Ca) or the polymer (Cb) is lower than 3.0 dL / g.
[0018] [3] The positive electrode active material layer according to [1] or [2], wherein the solid electrolyte (B) is an oxide-based solid electrolyte.
[0019] [4] The positive electrode active material layer according to [3], wherein the solid electrolyte (B) contains a material represented by the following formula (1).
[0020] Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 ……(1)
[0021] (In formula (1), x and y satisfy 0≤x≤1, 0≤y≤1).
[0022] [5] The positive electrode active material layer according to any one of [1] to [4], wherein the positive electrode active material (A) contains lithium metal phosphate, and the lithium metal phosphate is selected from LiFePO 4、LiMnPO 4 、LiCoPO 4 and LiNiPO 4 In the group formed.
[0023] [6] An electrode comprising a current collector and the positive electrode active material layer according to any one of [1] to [5].
[0024] [7] A semi-solid-state battery or an all-solid-state battery comprising the electrode described in [6].
[0025] Beneficial Effects
[0026] According to the present invention, there can be provided a positive electrode active material layer capable of forming a positive electrode with suppressed interface resistance between a current collector and an electrode active material, an electrode having the positive electrode active material layer, and a semi-solid battery or all-solid battery having the electrode. DETAILED DESCRIPTION
[0027] 《Positive electrode active material layer》
[0028] The positive electrode active material layer contains a positive electrode active material (A), a solid electrolyte (B) and a binder (C).
[0029] The binder (C) contained in the positive electrode active material layer is the following polymer (Ca) or polymer (Cb).
[0030] Polymer (Ca): a homopolymer of vinylidene fluoride having an intrinsic viscosity of 3.5 dL / g or less.
[0031] Polymer (Cb): A vinylidene fluoride copolymer containing structural units derived from vinylidene fluoride and structural units derived from hexafluoropropylene, wherein the intrinsic viscosity is 1.3 dL / g to 4.0 dL / g, and when all structural units of the vinylidene fluoride copolymer are 100% by weight, the structural units derived from hexafluoropropylene account for 8.0% by weight or less.
[0032] By making the positive electrode active material layer contain the specific binder (C), it is possible to form an electrode in which the interface resistance between the current collector and the positive electrode active material layer is suppressed.
[0033] Hereinafter, essential or optional components contained in the positive electrode active material layer will be described.
[0034] <Positive Electrode Active Material (A)>
[0035] The positive electrode active material (A) is not particularly limited, and for example, a conventionally known positive electrode active material can be used. As the positive electrode active material, a lithium-based positive electrode active material containing at least lithium is preferred. As the lithium-based positive electrode active material, for example, a positive electrode active material represented by the following formula (A-1) can be cited.
[0036] Li x M y O z ……(A-1)
[0037] (In formula (A-1), M is a transition metal element, x=0.02 to 2.2, y=1 to 2, z=1.4 to 4).
[0038] In formula (A-1), M may be at least one selected from the group consisting of Co, Mn, Ni, V, Fe and Si, or may be at least one selected from the group consisting of Co, Ni and Mn. Specifically, such a positive electrode active material may be: LiCoO 2 、LiMnO 2 、LiNiO 2 、LiVO 2 、LiMn 2 O 4 、Li(Ni 0.5 Mn 1.5 ) 4 , Li 2 FeSiO 4 , Li 2 MnSiO 4 wait.
[0039] As the positive electrode active material represented by the formula (A-1), from the viewpoint of suppressing the interface resistance between the current collector and the positive electrode active material layer, a lithium metal oxide represented by the following formula (A-2) is preferred.
[0040] LiNi x Co y Mn z O 2 ……(A-2)
[0041] (In formula (A-2), 0≤x≤1, 0≤y≤1, 0≤z≤1)
[0042] In formula (A-2), the composition ratio of x, y and z is, for example, preferably 0.3≤x≤0.8, 0.1≤y≤0.4, and 0.15≤z≤0.5, and more preferably 0.35≤x≤0.7, 0.1≤y≤0.35, and 0.2≤z≤0.45.
[0043] Examples of the lithium metal oxide represented by formula (A-2) include: LiNi 0.33 Co 0.33 Mn 0.33 (NCM111), LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), LiNi 0.5 Co 0.3 Mn 0.2 O 2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 (NCM811), LiCoO 2 (LCO), etc. Among them, LiNi is preferred 0.5 Co 0.2 Mn 0.3 O 2 (NCM523).
[0044] In addition, examples of positive electrode active materials (A) other than those of the above formula (A-1) include lithium titanate (e.g., Li 4 Ti 5 O 12 ), lithium metal phosphate (LiFePO 4 、LiMnPO 4 、LiCoPO 4 、LiNiPO 4 ), transition metal oxides (V 2 O 5 、MoO 3 )、TiS 2 、LiCoN、Si、SiO 2 , Li 2 SiO 3 , Li 4 SiO 4 and lithium-storing intermetallic compounds (such as Mg 2 Sn、Mg 2 Ge、Mg 2 Sb、Cu 3 Sb) etc. Among them, lithium phosphate is preferred from the viewpoint of suppressing the interface resistance between the current collector and the positive electrode active material layer. Among lithium phosphates, LiFePO 4 .
[0045] The shape of the positive electrode active material (A) is not particularly limited, and may be, for example, a particle shape or a thin film shape. From the viewpoint of good handling properties, the particle shape may also be used.
[0046] When the positive electrode active material is in the form of particles, the average particle size (D50) of the particles is, for example, preferably 1 nm or more and 100 μm or less, and more preferably 10 nm or more and 30 μm or less.
[0047] From the viewpoint of suppressing the reaction between the positive electrode active material and the solid electrolyte, a coating layer containing a Li ion conductive oxide may be formed on the surface of the positive electrode active material (A).
[0048] Examples of Li ion conductive oxides include LiNbO 3 , Li 4 Ti 5 O 12 and Li 3 PO 4 wait.
[0049] The lower limit of the thickness of the coating layer is preferably 0.1 nm or more, and more preferably 1 nm or more. The upper limit of the thickness of the coating layer is preferably 100 nm or less, and more preferably 20 nm or less.
[0050] The content of the positive electrode active material (A) is not particularly limited, but is preferably 50.0% by mass or more and 98.0% by mass or less, more preferably 60.0% by mass or more and 95.0% by mass or less, and further preferably 70.0% by mass or more and 90.0% by mass or less, relative to 100.0% by mass of the positive electrode active material layer.
[0051] <Solid Electrolyte (B)>
[0052] As the solid electrolyte (B), a sulfide-based solid electrolyte, an oxide-based solid electrolyte, etc. can be used. Among them, an oxide-based solid electrolyte is preferably used from the viewpoint of safety and stability of the electrolyte.
[0053] Examples of sulfide-based solid electrolytes include Li 2 S-SiS 2 、LiI-Li 2 S-SiS 2 、LiI-Li 2 SP 2 S 5 、LiI-Li 2 O-Li 2 SP 2 S 5 、LiI-Li 2 SP 2 O5 、LiI-Li 3 PO 4 -P 2 S 5 , Li 2 SP 2 S 5 and Li 3 PS 4 wait.
[0054] Examples of oxide-based solid electrolytes include LLTO-based compounds ((La, Li)TiO 3 )、Li 6 La 2 CaTa 2 O 12 , Li 6 La 2 ANb 2 O 12 (A: alkaline earth metal), Li 2 Nd 3 T8h 12 , Li 3 BO 2.5 N 0.5 , Li 9 SiAlO 8 LAGP compounds (Li 1+x Al x Ge 2-x (PO4) 3 (0≤x≤1))、Li 2 O-Al 2 O 3 -TiO 2 -P 2 O 5 Such LATP compounds (Li 1+ x Al x Ti 2-x (PO 4 ) 3 (0≤x≤1))、Li 1+x Ti 2-x Al x Si y (PO 4 ) 3-y (0≤x≤1,0≤y≤1), Li 1+y Al x M 2-x (PO 4 ) 3(M is one or more elements selected from the group consisting of Ti, Ge, Sr, Sn, Zr and Ca, 0≤x≤1, 0≤y≤1), LiTi x Zr 2-x (PO 4 ) 3 (0≤x≤1), LISICON(Li 4-2x Zn x GeO 4 (0≤x≤1)), LIPON compounds (Li 3+ y PO 4-x N x (0≤x≤1, 0≤y≤1)), NASICON compounds (LiTi 2 (PO 4 ) 3 etc.), garnet compounds (Li 7 La 3 Zr 2 O 12 , Li 7-x La 3 Zr 1-x Nb x O 12 (0≤x≤1) etc.
[0055] Among oxide-based solid electrolytes, LATP-based compounds are preferred from the viewpoint of having high lithium ion conductivity. As the LATP-based compound, a LATP-based compound containing a material represented by the following formula (1) is preferred.
[0056] Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 ……(1)
[0057] (In formula (1), x and y satisfy 0≤x≤1, 0≤y≤1).
[0058] In addition, examples of preferred oxide-based solid electrolytes other than the above-mentioned LATP-based compounds include: Li 7 La 3 Zr 2 O 12 (LLZO), Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 (LLZTO), Li 0.33 La 0.56 TiO3 (LLTO), Li 1.6 Al 0.6 Ge 1.4 (PO 4 ) 3 (LAGP) etc.
[0059] The content of the solid electrolyte (B) is not particularly limited, but is preferably 1.0 mass % to 40.0 mass % based on 100.0 mass % of the positive electrode active material layer, more preferably 2.0 mass % to 20.0 mass %, and further preferably 5.0 mass % to 15.0 mass %.
[0060] <Binder (C)>
[0061] The binder (C) is the following polymer (Ca) or polymer (Cb).
[0062] Polymer (Ca): a homopolymer of vinylidene fluoride having an intrinsic viscosity of 3.5 dL / g or less.
[0063] Polymer (Cb): A vinylidene fluoride copolymer containing structural units derived from vinylidene fluoride and structural units derived from hexafluoropropylene, wherein the intrinsic viscosity is 1.3 dL / g to 4.0 dL / g, and when all structural units of the vinylidene fluoride copolymer are 100.0% by weight, the structural units derived from hexafluoropropylene are 8.0% by weight or less.
[0064] The polymer (Ca) or the polymer (Cb) is used to suppress the interface resistance between the current collector and the positive electrode active material layer.
[0065] In addition, below, when there is no need to distinguish between the polymer (Ca) and the polymer (Cb), they will be simply described as "binder (C)".
[0066] (Polymer (Ca))
[0067] From the viewpoint of suppressing the interface resistance between the current collector and the positive electrode active material layer, the upper limit of the intrinsic viscosity of the polymer (Ca) is 3.5 dL / g or less, preferably less than 3.0 dL / g, and more preferably less than 2.5 dL / g.
[0068] The lower limit of the intrinsic viscosity of the polymer (Ca) is not particularly limited, and from the viewpoint of manufacturing, it is preferably 0.3dL / g or more, and more preferably 0.5dL / g or more. That is, when making a polymer (Ca) with an intrinsic viscosity less than 0.3dL / g, it is necessary to reduce the concentration of the monomer, or excessively use a chain transfer agent described later. If polymerization is carried out under such conditions, the polymerization rate becomes very slow, and in addition, when carrying out suspension polymerization described later, it is sometimes difficult to maintain suspension stability.
[0069] (Polymer (Cb))
[0070] As long as the effect of the present invention is not impaired, the structural unit of the polymer (Cb) may also contain structural units derived from other monomers different from the above-mentioned vinylidene fluoride (VDF) and hexafluoropropylene (HFP). As such other monomers, for example, monomers (preferably carboxyl-containing monomers) having polar functional groups with hydrogen bonding properties are included. Examples of carboxyl-containing monomers that can be copolymerized with vinylidene fluoride include unsaturated monobasic acids such as acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, and 2-carboxyethyl methacrylate; unsaturated dibasic acids such as maleic acid and citraconic acid; monoesters of unsaturated dibasic acids such as monomethyl maleate, monoethyl maleate, monomethyl citraconic acid, and monoethyl citraconic acid; acryloxyethyl succinic acid, acryloxypropyl succinic acid, methacryloyloxyethyl succinic acid, and methacryloyloxypropyl succinic acid.
[0071] When all the structural units of the polymer (Cb) are taken as 100% by mass, the content of the structural units derived from hexafluoropropylene (HFP) in the polymer (Cb) is 8.0% by mass or less, preferably 7.5% by mass or less.
[0072] When the polymer (Cb) contains a structural unit derived from monomethyl maleate (MMM), the content of the structural unit is not particularly limited, but is preferably 1.0 mass % or less, more preferably 0.6 mass % or less, based on 100 mass % of all the structural units of the polymer (Cb).
[0073] From the viewpoint of suppressing the interface resistance between the current collector and the positive electrode active material layer, the upper limit of the intrinsic viscosity of the polymer (Cb) is 4.0 dL / g or less, preferably less than 3.0 dL / g, and more preferably less than 2.5 dL / g.
[0074] From the viewpoint of suppressing the interface resistance between the current collector and the positive electrode active material layer, the lower limit of the intrinsic viscosity of the polymer (Cb) is 1.3 dL / g or more, and more preferably 1.6 dL / g or more.
[0075] The polymer (Ca) and the polymer (Cb) may be used alone or in combination.
[0076] The content of the binder (C) is not particularly limited, but is preferably 1.0% by mass to 40.0% by mass, more preferably 2.0% by mass to 30.0% by mass, and further preferably 3.0% by mass to 20.0% by mass, relative to 100.0% by mass of the positive electrode active material layer.
[0077] (Method for producing adhesive (C))
[0078] The method for producing the binder (C) is not particularly limited, and is generally carried out by suspension polymerization, emulsion polymerization, solution polymerization, etc. From the viewpoint of ease of post-treatment, aqueous suspension polymerization and emulsion polymerization are preferred, and aqueous suspension polymerization is more preferred.
[0079] The aqueous suspension polymerization method is not particularly limited, and examples thereof include a method in which monomers used for polymerization are polymerized in an aqueous medium in the presence of a suspending agent, a polymerization initiator, a chain transfer agent, and the like.
[0080] The suspending agent is not particularly limited, and examples thereof include methylcellulose, methoxylated methylcellulose, propoxylated methylcellulose, hydroxyethyl methylcellulose, hydroxypropyl methylcellulose, polyvinyl alcohol, polyethylene oxide, gelatin, etc. The amount of the suspending agent used is not particularly limited, and for example, is preferably 0.005 parts by mass or more and 1.0 parts by mass or less, and more preferably 0.01 parts by mass or more and 0.4 parts by mass or less, relative to 100 parts by mass of all monomers used in the polymerization.
[0081] As polymerization initiator, it is not particularly limited, for example, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di-n-heptafluoropropyl peroxydicarbonate, isobutyryl peroxide, di(chlorofluoroacyl) peroxide, di(perfluoroacyl) peroxide, and tert-butyl peroxypivalate etc. can be listed. The usage amount of polymerization initiator is not particularly limited, for example, relative to 100.0 mass parts of all monomers used in the polymerization, preferably more than 0.05 mass part and less than 5.0 mass parts, more preferably more than 0.15 mass part and less than 2.0 mass parts.
[0082] The chain transfer agent is not particularly limited, and examples thereof include ethyl acetate, propyl acetate, acetone, and diethyl carbonate.
[0083] In addition, the amount of monomers used in the polymerization is calculated as the mass ratio of the total monomers to water, which is usually 1:1 to 1:10, preferably 1:2 to 1:5. The polymerization conditions such as the polymerization temperature and polymerization time when performing suspension polymerization are not particularly limited, and for example, known polymerization conditions can be used. The polymerization temperature T can be appropriately selected based on the 10-hour half-life temperature T10 of the polymerization initiator, and is usually selected within the range of T10-25°C ≤ T ≤ T10 + 25°C. For example, the T10 of tert-butyl peroxypivalate and diisopropyl peroxydicarbonate are 54.6°C and 40.5°C, respectively (refer to the product catalog of NOF Corporation). Therefore, when tert-butyl peroxypivalate and diisopropyl peroxydicarbonate are used as polymerization initiators for polymerization, the polymerization temperature T is selected within the range of 29.6°C ≤ T ≤ 79.6°C and 15.5°C ≤ T ≤ 65.5°C, respectively. The polymerization time is not particularly limited, and if productivity, etc. are taken into consideration, it is preferably 1 to 24 hours.
[0084] <Other ingredients>
[0085] As long as the effect of the present invention is not impaired, the positive electrode active material layer may also contain components other than the above-mentioned positive electrode active material (A), solid electrolyte (B) and binder (C) (hereinafter also referred to as "other components"). As other components, all known additives can be used, for example, conductive additives, insulating inorganic fillers such as aluminum oxide, magnesium oxide, and silicon dioxide, insulating organic fillers such as polytetrafluoroethylene, polyimide, and polyacrylonitrile, plasticizers such as ethylene carbonate, propylene carbonate, and ethyl methyl carbonate, LiPF 6 , Li salts such as LiFSI, LiTFSI, dispersants, flame retardants, defoaming agents, etc.
[0086] Examples of the conductive additive (D) include carbon black and carbon nanotubes, etc. These may be used alone or in combination of two or more.
[0087] The content of the conductive aid (D) is not particularly limited, but is preferably 0.05 mass % to 15.0 mass % based on 100.0 mass % of the positive electrode active material layer, more preferably 0.1 mass % to 10.0 mass %, and further preferably 0.5 mass % to 8.0 mass %.
[0088] "electrode"
[0089] The electrode is a positive electrode and includes a current collector and the positive electrode active material layer described above.
[0090] By including the positive electrode active material layer, the electrode exhibits an effect of suppressing the interface resistance between the current collector and the positive electrode active material layer.
[0091] (Current Collector)
[0092] The current collector is a terminal for taking out electricity. The material of the current collector is not particularly limited, and metal foil or metal mesh of aluminum, copper, iron, stainless steel, steel, nickel, titanium, etc. can be used. In addition, it can also be a material formed by applying the above-mentioned metal foil or metal mesh on the surface of other media.
[0093] The volume density of the electrode is not particularly limited, but is preferably 1.5 g / cm 3 Above and 5.0g / cm 3 the following.
[0094] The weight per unit area of the electrode is not particularly limited, but is preferably 20 g / m 2 Above and 1000g / m 2 the following.
[0095] 《Electrode manufacturing method》
[0096] As a method for manufacturing an electrode, for example, there can be cited a method including the following steps: a step of mixing the above-mentioned positive electrode active material (A), solid electrolyte (B), binder (C), other components as required, and non-aqueous solvent (S) to prepare a positive electrode slurry; a step of applying the obtained positive electrode slurry to a collector and then drying it. That is, in the above-mentioned embodiment, after the step of drying the positive electrode slurry, the positive electrode active material layer is prepared, and the electrode is also prepared.
[0097] Examples of the non-aqueous solvent (S) include N-methyl-2-pyrrolidone (hereinafter referred to as "NMP"), dimethylformamide, N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N,N-dimethyl sulfoxide, hexamethylphosphoramide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate, trimethyl phosphate, acetone, cyclohexanone, methyl ethyl ketone, and tetrahydrofuran. These may be used alone or in combination of two or more.
[0098] The coating method is not particularly limited, and for example, a doctor blade method, a reverse roll method, a comma bar method, a gravure printing method, an air knife method, a die coating method, a dip coating method, and the like can be applied.
[0099] The drying temperature is, for example, preferably 80° C. or higher and 300° C. or lower, more preferably 90° C. or higher and 200° C. or lower, and further preferably 100° C. or higher and 180° C. or lower.
[0100] The drying time is, for example, preferably 10 seconds to 300 minutes, more preferably 1 minute to 200 minutes.
[0101] Drying can be performed multiple times at different temperatures. During drying, pressure can be applied.
[0102] All-solid-state battery
[0103] The all-solid-state battery includes the electrode of the above-described embodiment. As the all-solid-state battery, conventionally known components can be used for components other than the positive electrode, such as the negative electrode and the separator.
[0104] Semi-solid-state battery
[0105] The semi-solid battery has the electrode of the above embodiment. As a semi-solid battery, parts other than the positive electrode, such as the negative electrode, the separator, etc., can use conventionally known parts. When the volume of the electrolyte contained in the conventional secondary battery containing the electrolyte is set to 100.0%, the amount of electrolyte contained in the semi-solid battery is preferably 1.0 to 95.0%, more preferably 1.0 to 90.0%, and further preferably 1.0 to 80.0%.
[0106] Example
[0107] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0108] [Examples 1 to 10 and Comparative Examples 1 to 5]
[0109] <Materials used>
[0110] In the examples and comparative examples, the following A1 to A2 were used as the positive electrode active material (A).
[0111] A1: LiFePO 4 .
[0112] A2:NCM5232.
[0113] In Examples and Comparative Examples, the following B1 was used as the solid electrolyte (B).
[0114] B1: Li 1+x+y Al x Ti 2x Si y P 3y O 12 (LATP)(OHARA Corporation, "LICGC TM PW-01 (particle size 1 μm)”).
[0115] In the examples and comparative examples, the following C1 to C12 were prepared and used as the adhesive (C). In addition, the intrinsic viscosity of each prepared adhesive was measured by the following method.
[0116] (Determination of intrinsic viscosity)
[0117] 80 mg of each binder was dissolved in 20 ml of N,N-dimethylformamide to prepare a binder-containing solution. Then, the viscosity η of the binder-containing solution was measured in a 30°C constant temperature bath using an Ubbelohde viscometer. 1 Similarly, the viscosity η of N,N-dimethylformamide was measured in a 30°C constant temperature bath using an Ubbelohde viscometer. 0 Then, the intrinsic viscosity η was calculated based on the following formula.
[0118] Intrinsic viscosity η=(1 / C)·ln(η 1 / η 0 )
[0119] (Preparation Example of Adhesive C1 (PVDF))
[0120] Into a 2-liter autoclave, 253.0 parts by mass of ion exchange water, 0.0.5 parts by mass of methylcellulose, 100 parts by mass of vinylidene fluoride (VDF), 0.6 parts by mass of di-n-propyl peroxydicarbonate, 0.6 parts by mass of methanol, and 1.4 parts by mass of ethyl acetate were charged, and polymerization was started at 26°C. Then, the temperature was raised and suspension polymerization was carried out at 40°C for 12 hours. After the polymerization was completed, the obtained polymer slurry was heat-treated at 95°C for 30 minutes, dehydrated, washed with water, and further dried at 80°C for 20 hours to obtain adhesive C1. In adhesive C1, 100.0% by mass of VDF is contained relative to all structural units. The intrinsic viscosity (η) of adhesive C1 is 1.1dL / g.
[0121] (Preparation Example of Adhesive C2 (PVDF))
[0122] Into a 2-liter autoclave were placed 231.8 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 100 parts by mass of VDF, 0.7 parts by mass of diisopropyl peroxydicarbonate (IPP), and 0.7 parts by mass of ethyl acetate, and VDF was polymerized by the same method as in the preparation example of adhesive C1 to obtain adhesive C2. Adhesive C2 contained 100.0% by mass of VDF relative to all structural units. The intrinsic viscosity (η) of adhesive C2 was 2.1 dL / g.
[0123] (Preparation Example of Adhesive C3 (PVDF))
[0124] VDF was polymerized by the same method as in the preparation example of adhesive C2, except that the amount of ion exchange water charged was changed to 213.8 parts by mass, the amount of IPP charged was changed to 0.3 parts by mass, and the amount of ethyl acetate charged was changed to 0.42 parts by mass, to obtain adhesive C3. Adhesive C3 contained 100.0% by mass of VDF relative to all structural units. The intrinsic viscosity (η) of adhesive C3 was 3.1 dL / g.
[0125] (Preparation Example of Adhesive C4 (PVDF))
[0126] VDF was polymerized by the same method as in the preparation example of adhesive C1, except that the loading amount of ion exchange water was changed to 312.5 parts by mass, the loading amount of diethyl carbonate was changed to 3.5 parts by mass, VDF was 100 parts by mass, tert-butyl peroxypivalate was 0.13 parts by mass, and the loading amount of ethyl acetate was changed to 0.1 parts by mass, to obtain adhesive C4. Adhesive C4 contained 100.0% by mass of VDF relative to all structural units. The intrinsic viscosity (η) of adhesive C4 was 0.3 dL / g.
[0127] (Preparation Example of Adhesive C5 (VDF / HFP))
[0128] 290 parts by mass of ion exchange water, 0.15 parts by mass of methylcellulose, 57.9 parts by mass of vinylidene fluoride (VDF), 7.8 parts by mass of hexafluoropropylene (HFP), and 0.9 parts by mass of diisopropyl peroxydicarbonate were added to an autoclave with a volume of 2L, and polymerized at 45°C. 34.3 parts by mass of VDF were added to obtain a copolymer. After the obtained copolymer was heat-treated at 95°C for 60 minutes, it was dehydrated and washed with water, and then dried at 80°C for 20 hours to obtain an adhesive C5. In the adhesive C5, 94.3% by mass of VDF and 5.7% by mass of HFP were contained relative to the total amount of structural units. The intrinsic viscosity (η) of the adhesive C5 is 1.5dL / g.
[0129] (Production Example of Adhesive C6 (VDF / HFP))
[0130] Adhesive C6 was obtained by polymerizing VDF and HFP in the same manner as in the preparation example of Adhesive C1 except that 253.0 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 90.0 parts by mass of VDF, 10.0 parts by mass of HFP, 0.4 parts by mass of IPP, and 1.0 parts by mass of ethyl acetate were used. Adhesive C6 contained 93.0% by mass of VDF and 7.0% by mass of HFP relative to all structural units. The intrinsic viscosity (η) of Adhesive C6 was 1.9 dL / g.
[0131] (Production Example of Adhesive C7 (VDF / HFP / MMM))
[0132] Adhesive C7 was obtained by polymerizing VDF, HFP and MMM in the same manner as in the preparation example of adhesive C1 except that 240.2 parts by mass of ion exchange water, 0.2 parts by mass of methylcellulose, 96.7 parts by mass of VDF, 3.0 parts by mass of HFP, 0.3 parts by mass of monomethyl maleate (MMM) and 0.47 parts by mass of IPP were used. It should be noted that the amount of each monomer in adhesive C7 was determined as follows: the VDF / HFP ratio was calculated by 19F-NMR, the VDF / MMM ratio was determined by the following method, and then the total of VDF, HFP and MMM was calculated to be 100 mol%.
[0133] The VDF / MMM ratio (the molar ratio of the amount of structural units derived from vinylidene fluoride to the amount of structural units derived from monomethyl maleate) in the copolymer was calculated based on the calculation method using the IR spectrum and the standard curve disclosed in International Publication No. 2009 / 084483. In the adhesive C7, 97.4% by mass of VDF, 2.3% by mass of HFP, and 0.3% by mass of MMM were contained relative to all structural units. In addition, the intrinsic viscosity (η) of the adhesive C7 was 3.0 dL / g.
[0134] (Preparation Example of Adhesive C8 (VDF / CTFE))
[0135] Adhesive C8 was obtained by polymerizing VDF and CTFE in the same manner as in the preparation example of Adhesive C1, except that 256.6 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 96.0 parts by mass of VDF, 4.0 parts by mass of chlorotrifluoroethylene (CTFE), 0.6 parts by mass of IPP, and 0.59 parts by mass of ethyl acetate were used. In Adhesive C8, 96.0% by mass of VDF and 4.0% by mass of CTFE were contained relative to all structural units. The intrinsic viscosity (η) of Adhesive C8 is 2.1dL / g. (Preparation Example of Adhesive C9 (VDF / HFP / MMM))
[0136] Adhesive C9 was obtained by polymerizing VDF, HFP and MMM in the same manner as in the preparation example of Adhesive C1 except that 259.0 parts by mass of ion exchange water, 0.2 parts by mass of methylcellulose, 90 parts by mass of VDF, 10 parts by mass of HFP, 0.5 parts by mass of MMM, 2.0 parts by mass of IPP and 0.17 parts by mass of ethyl acetate were used. Adhesive C9 contained 93.3% by mass of VDF, 6.2% by mass of HFP and 0.5% by mass of MMM relative to all structural units. The intrinsic viscosity (η) of Adhesive C9 was 1.2 dL / g.
[0137] (Production Example of Adhesive C10 (VDF / HFP / MMM))
[0138] Adhesive C10 was obtained by polymerizing VDF, HFP and MMM in the same manner as in the preparation example of adhesive C1 except that 243.1 parts by mass of ion exchange water, 0.2 parts by mass of methylcellulose, 86.0 parts by mass of VDF, 13.5 parts by mass of HFP, 0.5 parts by mass of MMM and 1.77 parts by mass of IPP were used. Adhesive C10 contained 89.5% by mass of VDF, 10.0% by mass of HFP and 0.5% by mass of MMM relative to all structural units. The intrinsic viscosity (η) of adhesive C10 was 1.5 dL / g.
[0139] (Preparation Example of Adhesive C11 (PVDF))
[0140] Adhesive C11 was obtained by polymerizing VDF in the same manner as in the preparation example of Adhesive C1, except that 217 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 100 parts by mass of VDF, 0.09 parts by mass of IPP, and 0.25 parts by mass of ethyl acetate were used. Adhesive C11 contained 100.0% by mass of VDF relative to all structural units. The intrinsic viscosity (η) of Adhesive C11 was 4.2 dL / g.
[0141] (Production Example of Adhesive C12 (VDF / HFP))
[0142] Adhesive C12 was obtained by polymerizing VDF and HFP in the same manner as in the preparation example of Adhesive C1, except that 256.0 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 90.0 parts by mass of VDF, 10 parts by mass of HFP, 0.1 parts by mass of IPP, and 0.2 parts by mass of ethyl acetate were used. Adhesive C12 contained 93.0% by mass of VDF and 7.0% by mass of HFP relative to all structural units. The intrinsic viscosity (η) of Adhesive C12 was 4.4 dL / g.
[0143] Table 1 shows the detailed information of the obtained adhesives C1 to C12.
[0144] [Table 1]
[0145]
[0146] In Examples and Comparative Examples, the following D1 to D2 were used as the conductive auxiliary agent (D).
[0147] D1: Carbon nanotube (CNT) dispersion.
[0148] D2:SuperP.
[0149] In Examples and Comparative Examples, S1 described below was used as the nonaqueous solvent (S).
[0150] S1: N-methyl-2-pyrrolidone (NMP).
[0151] (Preparation of positive electrode slurry)
[0152] Each binder (C) was dispersed in N-methyl-2-pyrrolidone (NMP) at room temperature so that the concentration of the binder (C) became an arbitrary concentration, and then the solution temperature was raised to 50°C to dissolve each binder (C) (hereinafter referred to as "binder solution"). The positive electrode active material (A), the solid electrolyte (B), the conductive additive (D) and the above-mentioned binder solutions were used to mix the components in a manner to obtain the contents described in Table 2 below. The solid content of the positive electrode slurry was adjusted using NMP.
[0153] (Fabrication of positive electrode)
[0154] Each of the obtained positive electrode slurries was applied to an Al foil (thickness 15 μm), and then dried at 120° C. Each of the obtained preliminary positive electrodes was pressed and further heat treated at 120° C. for 3 hours. 4 When used as an active material, the electrode volume density is 2.3 g / cm 3 When NCM523 is used as the active material, the electrode volume density is 3.3 g / cm 3 The weight per unit area was 200 g / m2 when any active material was used. 2 of each positive electrode.
[0155] <Evaluation>
[0156] The electrode resistance of each of the obtained positive electrodes was measured by the following method.
[0157] (Interface resistance)
[0158] Each positive electrode was punched into Φ14 mm pieces to produce three test samples. Electrode resistance measurement system RM2610 (Hioki Electric Co., Ltd.) was used to measure 5 points on each test sample. The interface resistance (Ω·cm) was calculated from the average value of the 15 measurement data. 2 ). The results are shown in Table 2.
[0159] [Table 2]
[0160]
[0161]
[0162] According to Table 2, in the positive electrode of Comparative Example 4 having a positive electrode active material layer including a binder C11 (PVDF) having an intrinsic viscosity exceeding 3.5 dL / g, the interface resistance is as high as 1.03 Ω·cm. 2 On the other hand, in the positive electrode having a positive electrode active material layer containing binders C1 to C4 (all PVDF) with an intrinsic viscosity of 3.5 dL / g or less, as shown in Examples 1 to 4, the maximum interface resistance is only 0.50 Ω·cm 2 It can be seen that the interface resistance between the current collector and the electrode active material has been greatly suppressed.
[0163] In addition, in the positive electrodes of Comparative Examples 2, 3, and 5 having a positive electrode active material layer including a binder C9 (VDF / HFP / MMM) having an intrinsic viscosity of less than 1.3 dL / g, a binder C12 (VDF / HFP) having an intrinsic viscosity of more than 4.0 dL / g, and a binder C10 (VDF / HFP / MMM) having a structural unit derived from HFP of more than 8% by mass, the minimum interface resistance remained at 0.79 Ω·cm 2 .
[0164] On the other hand, in the positive electrode having a positive electrode active material layer containing binders C5 to C6 (VDF / HFP) and C7 (VDF / HFP / MMM) having an intrinsic viscosity of 1.3 dL / g or more and 4.0 dL / g or less and a structural unit derived from HFP of 8% by mass or less, as shown in Examples 5 to 7, the maximum interface resistance was only 0.56 Ω·cm 2 , it can be seen that the interface resistance between the current collector and the electrode active material is suppressed.
[0165] On the other hand, in the positive electrode having a positive electrode active material layer including a binder C8 (VDF / CTFE) that satisfies the above-mentioned intrinsic viscosity range but contains a structural unit derived from CTFE instead of HFP, as shown in Comparative Example 1, the interface resistance remains at 0.74 Ω·cm 2 .
Claims
1. A positive electrode active material layer, comprising a positive electrode active material (A), a solid electrolyte (B) and a binder (C), wherein: The binder (C) is the following polymer (Ca) or polymer (Cb), Polymer (Ca): a homopolymer of vinylidene fluoride having an intrinsic viscosity of 3.5 dL / g or less, Polymer (Cb): a vinylidene fluoride copolymer containing structural units derived from vinylidene fluoride and structural units derived from hexafluoropropylene, having an intrinsic viscosity of 1.3 dL / g to 4.0 dL / g, wherein the structural units derived from hexafluoropropylene account for 8.0% by mass or less, based on 100.0% by mass of all structural units of the vinylidene fluoride copolymer.
2. The positive electrode active material layer according to claim 1, wherein The intrinsic viscosity of the polymer (Ca) or the polymer (Cb) is lower than 3.0 dL / g.
3. The positive electrode active material layer according to claim 1 or 2, wherein The solid electrolyte (B) is an oxide-based solid electrolyte.
4. The positive electrode active material layer according to claim 3, wherein The solid electrolyte (B) comprises a material represented by the following formula (1): There 1+x+y To the x You 2-x Yes y P 3-y OR 12 ……(1) In formula (1), x and y satisfy 0≤x≤1, 0≤y≤1.
5. The positive electrode active material layer according to claim 1 or 2, wherein The positive electrode active material (A) contains lithium metal phosphate, The lithium metal phosphate is selected from the group consisting of LiFePO 4 , LiMnPO 4 , LiCoPO 4 and LiNiPO 4 . 6 . An electrode comprising a current collector and the positive electrode active material layer according to claim 1 or 2 .
7. A semi-solid-state battery or an all-solid-state battery, comprising the electrode according to claim 6.
Citation Information
Patent Citations
Positive electrode material for solid battery, manufacturing method thereof, all-solid lithium sulfur battery arranged by use of positive electrode material for solid battery, and manufacturing method thereof
JP2017168435A